2018
DOI: 10.7754/clin.lab.2018.180105
|View full text |Cite
|
Sign up to set email alerts
|

Serum Soluble ST2 as a Novel Inflammatory Marker in Acute Ischemic Stroke

Abstract: Background: Soluble ST2 (sST2) receptor is secreted and detectable in human serum, which acts as a decoy receptor for interleukin (IL)-33 to prevent IL-33-mediated Th2 immune responses. Recently, elevated serum sST2 has been found to be a novel biomarker in cardiovascular diseases such as heart failure and atherosclerosis. Here, we studied the role of sST2 in acute ischemic stroke (AIS) and its relationship with several inflammatory markers. Methods: The study included 112 patients with first-ever acute ischem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 29 publications
3
14
0
1
Order By: Relevance
“…A recent study found that sST2 levels were higher when cerebral infarct volumes, NIHSS scores, and high sensitivity C-reactive protein levels were increased [23]. Our results on the association between serum sST2 and the severity of TIA/ischemic stroke agreed with these, further verifying this potential marker in patients with TIA/ischemic stroke and suggesting that sST2 may be an indicator for risk stratification in TIA/ischemic stroke.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A recent study found that sST2 levels were higher when cerebral infarct volumes, NIHSS scores, and high sensitivity C-reactive protein levels were increased [23]. Our results on the association between serum sST2 and the severity of TIA/ischemic stroke agreed with these, further verifying this potential marker in patients with TIA/ischemic stroke and suggesting that sST2 may be an indicator for risk stratification in TIA/ischemic stroke.…”
Section: Discussionsupporting
confidence: 87%
“…For instance, one small study found a markedly higher proportion of AIS patients with high sST2 levels compared to healthy controls when sST2 was dichotomized by a cut point (n = 53 vs. 12, P = 0.037) [8]. Another study reported that serum ST2 levels were markedly upregulated in AIS patients versus controls (n = 112 vs. 78, P<0.01) [23]. Accordingly, we finally measured and analyzed serum sST2 levels in this study.…”
Section: Discussionmentioning
confidence: 96%
“…Hyperlipidemia, one of the most important risk factors account for the further development of atherosclerosis, can activate the JAK/STAT signaling of vascular endothelial cells through phosphorylation of JAK2 and subsequently STAT3, leading to the deterioration of atherosclerosis [24]. AIP acts as a critical mark of atherosclerosis because the deposition of foam cells or plaque or fatty in filtration or lipids in organs could be indicated by it [25]. In this study, a 12-week high-fat diet feeding accompanied by balloon injury of the aorta not only resulted in the increase in TG, TC and LDL-C contents and AIP value, but also led to the obvious lipid burden in atherosclerotic plaques when compared with the normal control rabbit.…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that patients with AIS had significantly higher levels of serum sST2 than controls. Further, higher sST2 levels were associated with increased cerebral infarct volumes, NIHSS score and high‐sensitivity C‐reactive protein in AIS [23]. However, there remain limited data regarding the effect of sST2 levels on long‐term prognosis in ischaemic cerebrovascular disease.…”
Section: Discussionmentioning
confidence: 99%